THE ROLE OF THEATERAL ART IN INCREASING THE SOCIAL ACTIVITY OF YOUTH IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
In this article, philosophical factors in increasing the social activity of youth and the development of theatrical art at the stage of social development of the new Uzbekistan, as well as the process of influencing human life, especially the sustainable development of society, are investigated in many scientific studies. In increasing the social activity of young people, with a sense of developing an aesthetic worldview based on theatrical art, not only seeing beauty as a personal experience, but also introducing young people to our national culture and traditions in the social development of society, the results and new ideas of awakening love for the nation are highlighted.